2016
DOI: 10.1007/s10101-016-0181-5
|View full text |Cite|
|
Sign up to set email alerts
|

Policies against human trafficking: the role of religion and political institutions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 107 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Human trafficking researchers discuss law enforcement and the level of corruption as important factors, both in origin and destination countries (Akee et al 2010(Akee et al , 2014Cho, Dreher, & Neumayer, 2013;Jakobsson & Kotsadam, 2013). Besides the general rule of law, specific antitrafficking measures are also crucial to addressing the problem (Cho et al 2014;Cho & Vadlamannati, 2012;Potrafke, 2013). The anti-trafficking measures include prosecution policy against traffickers, protection policy for victims, and prevention policy (UN, 2000).…”
Section: Policy and Institutional Effortsmentioning
confidence: 99%
“…Human trafficking researchers discuss law enforcement and the level of corruption as important factors, both in origin and destination countries (Akee et al 2010(Akee et al , 2014Cho, Dreher, & Neumayer, 2013;Jakobsson & Kotsadam, 2013). Besides the general rule of law, specific antitrafficking measures are also crucial to addressing the problem (Cho et al 2014;Cho & Vadlamannati, 2012;Potrafke, 2013). The anti-trafficking measures include prosecution policy against traffickers, protection policy for victims, and prevention policy (UN, 2000).…”
Section: Policy and Institutional Effortsmentioning
confidence: 99%
“…10, No. 2;2018 empirical results indicate that as the poorest become marginally better off there is an increase in human trafficking outflow. It is hypothesized that as the poor make some economic gains, these gains could be used to acquire technology and/or means of travel that can connect them to the world outside of their immediate, impoverished surroundings.…”
Section: Resultsmentioning
confidence: 99%
“…10, No. 2;2018 empirical evidence at both the survey, micro-level and at a macro-level in Nepal that greater relative deprivation significantly increases trafficking incidences. It is important to note that the sense that one"s wealth falls below a point of reference, or the perceived relative deprivation, is formed through comparisons of the lives of others.…”
Section: Review Of European Studiesmentioning
confidence: 98%
“…Different levels of compliance with the UN Anti-Trafficking Protocol have attracted scholars' attention [8,9,15,16,[26][27][28][29][30]. This research has identified a set of factors that drive states' efforts to prosecute and prevent human trafficking as well as to protect its victims.…”
Section: Explaining Anti-trafficking Effortsmentioning
confidence: 99%
“…Hence, understanding what drives the enforcement of victim protection policies warrants a closer examination of domestic legislators, which are responsible for policymaking. While studies have repeatedly established a positive link between anti-trafficking efforts and the representation of women in national parliaments as well as respect for the rights of women in society [8,9,12,14,16], there are currently no studies which have analysed characteristics of parliaments and governments beyond the representation of women in political institutions. Consequently we know little about how the ideological composition of governments and parliaments shape victim protection efforts of nation states and whether the positive association between the percentage of female parliamentarians and compliance with anti-trafficking treaties remains significant when other government characteristics are controlled for.…”
Section: Introductionmentioning
confidence: 99%